1999
DOI: 10.1002/(sici)1099-0682(199901)1999:1<83::aid-ejic83>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

2,4,6-Tri-tert-butyl-1,3,5-triphosphabenzene as an η6-Ligand in Transition Metal Complexes

Abstract: The η6‐1,3,5‐triphosphabenzene transition metal complexes 12a,b, 14, and 16 have been synthesized for the first time by the displacement of η6‐arene ligands (toluene, benzene and naphthalene) with 2,4,6‐tri‐tert‐butyl‐1,3,5‐triphosphabenzene (9). The new complexes have been fully characterized by a combination of elemental analysis, mass spectrometry, and 1H‐, 13C‐ and 31 P‐NMR spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Yield = 180 mg, 73%. 1 H NMR (400 MHz, CD 2 Cl 2 ): 8.10, 8.05 (m, ring H's), 1.96 (m, 6H, P{CH 2 CH 3 } 3 ), 1.79 (s, 18H, Bu t ), 1.39 (s, 9H, Bu t ), 1.27, 1.23 (2 overlapping t, 9H, P{CH 2 CH 3 } 3 , 7.61 Hz). 31 3 Â 10 À4 mol) and 5 (0.044 g, 6.5 Â 10 À5 mol) were combined, dissolved in toluene and stirred vigorously for 24 hours.…”
Section: Preparation Of Trans-[ptcl 2 (Pr 3 )(G 1 -Pc 5 H 2 Bu T 3 )]mentioning
confidence: 72%
See 1 more Smart Citation
“…Yield = 180 mg, 73%. 1 H NMR (400 MHz, CD 2 Cl 2 ): 8.10, 8.05 (m, ring H's), 1.96 (m, 6H, P{CH 2 CH 3 } 3 ), 1.79 (s, 18H, Bu t ), 1.39 (s, 9H, Bu t ), 1.27, 1.23 (2 overlapping t, 9H, P{CH 2 CH 3 } 3 , 7.61 Hz). 31 3 Â 10 À4 mol) and 5 (0.044 g, 6.5 Â 10 À5 mol) were combined, dissolved in toluene and stirred vigorously for 24 hours.…”
Section: Preparation Of Trans-[ptcl 2 (Pr 3 )(G 1 -Pc 5 H 2 Bu T 3 )]mentioning
confidence: 72%
“…Although previous studies have shown that the 2,4,6-tritertiarybutyl-1,3,5-triphosphabenzene ring 1 readily acts as a 6p-electron donor towards metal centres [1][2][3], the only reported examples of g 1 -bonded metal complexes are trans-[PtCl 2 (PR 3 )(g 1 -P 3 C 3 Bu t…”
Section: Introductionmentioning
confidence: 96%
“…In the light of that result, identity of the 31 P spin systems of diamagnetic 12 and radical 7 À is not accidental, but reflects the single respectively double occupancy of analogous orbitals, which cause the distortions of 7 À and 12. This finding represents a strong contrast to the formal Ru-analogue of 12 [(h 4 -1,5-COD)(h 6 -2,4,6-tri-tert-butyl-1,3,5-triphosphinine)Ru] (14) [15]. As for other (h 6 -2,4,6-tri-tert-butyl-1,3,5-triphosphinine)Ru complexes [29], 14 appears to be a classical (h 6 -1,3,5-triphosphinine)M (0) complex with a planar and C 3 -symmetric heteroarene ligand.…”
Section: Density Functional Theory (Dft) Calculationsmentioning
confidence: 99%
“…The calculated molecular structure of 8c(t) seems to be somewhat strange; however, it is isoenergetic with 8b(t) and there exists a case of precedence. A reversible interligand bond forming process of that kind has been observed between two of the p-ligands of tris(2,4-di-tertbutyl-1,3-diphosphete)Mo (15) [30]. This specific reactivity was rationalized as a consequence of a pronounced ambiphilicity of p-bound unsaturated P-heterocycles.…”
Section: [ ( F I G _ 4 ) T D $ F I G ]mentioning
confidence: 99%
See 1 more Smart Citation